DIGITAL LOYALTY FOR SOCIAL MEDIA, A CASE STUDY ON BOXPLOSIVE B.V. - Pandoyo, Christopher; Setiabudi, Djoni Haryadi (Jurnal Informatika, 2017)
Digital loyalty is the process of providing incentives to customers through digital media to increase customer loyalty. Nowadays, Boxplosive B.V. using app to distribute deal and saver cards from retailers like AH to go and Etos to their customer. But the problem is that not all the customers are willing to download the app. To overcome this problem, this research investigate how social media app can be used for distributing deal and saver card. Therefore, a prototype program will be built for the implementation to show that social media app can be used for business purposes. The result shows that now the customer do not need to download the separate apps to get the deas and saver card.